2021
DOI: 10.1212/cpj.0000000000001080
|View full text |Cite
|
Sign up to set email alerts
|

Review of Neurologic Comorbidities in Hospitalized Patients With Opioid Abuse

Abstract: Purpose of review:Determine the prevalence and burden of neurological comorbidities in hospitalized patients with opioid abuse.Recent findings:From one year of hospital discharges 2,182 opioid abuse patients were identified (prevalence 6.3%), with abuse greater among younger patients (p<0.0001), women (p<0.0001), whites (p<0.0001), and urban population (p=0.028). Matching for age, sex, race, and urban-rural residence, 347 patients were reviewed and 179 (52%) had a neurological comorbidity. The comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Neurologically, the effects of opioid overdose have been sparingly described. Nelson et al and Andalibi et al found that opioid abuse was associated with frequent comorbidities of encephalopathy, neuromuscular disorders, seizures, spine disorders, strokes, central nervous system (CNS) infections, and movement disorders, with opioid use disorder specifically increasing the hazard ratio of stroke mortality without an effect on the disability rate [ 7 , 8 ]. Birsic et al described the case of a 37-year-old female with a history of intravenous drug use who presented with extremity weakness and pain and was found to have large endocardial vegetation on both the tricuspid and mitral valves with a patent foramen ovale, prompting embolization of these vegetations into the lungs, liver, and brain [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurologically, the effects of opioid overdose have been sparingly described. Nelson et al and Andalibi et al found that opioid abuse was associated with frequent comorbidities of encephalopathy, neuromuscular disorders, seizures, spine disorders, strokes, central nervous system (CNS) infections, and movement disorders, with opioid use disorder specifically increasing the hazard ratio of stroke mortality without an effect on the disability rate [ 7 , 8 ]. Birsic et al described the case of a 37-year-old female with a history of intravenous drug use who presented with extremity weakness and pain and was found to have large endocardial vegetation on both the tricuspid and mitral valves with a patent foramen ovale, prompting embolization of these vegetations into the lungs, liver, and brain [ 9 ].…”
Section: Discussionmentioning
confidence: 99%